The Effect of Self-Care Education on Emotional Intelligence of Iranian Nursing Students: A Quasi-experimental Study - Goudarzian, Amir Hossein (Journal of religion and health, 2019)
This study aimed to determine the effect of self-care training on emotional intelligence of nursing students. This quasi-experimental study was conducted on nursing students of Mazandaran University of Medical Sciences in 2016. The subjects (60 students) that were collected with random sampling method were divided into experimental and control groups, and then, self-care behaviors were taught to the experimental group' students in 12 sessions by using a checklist. The subjects of control group were not taught. Emotional intelligence was measured by using Bradberry and Greaves' standard questionnaire before and after the intervention. Emotional intelligence scores of students in the experimental group showed positive and significant change between before (75.33 ± 7.23) and after (125.70 ± 7.79) of training (P < 0.001). Also t test shows a significant change in control (78.73 ± 6.54) and experimental groups (125.70 ± 7.79), after of training (P < 0.001). It is recommended that special programs be organized in order to improve the emotional intelligence of students that improve the likelihood of their success in life.